Nutritional Status of Children Aged 5-10 Years, Reporting to the Government Tertiary Hospital in Mandya - Mythily, M R; Vinay, M; Harish, B R (National Journal of Community Medicine, 2020)
Introduction: Malnutrition is a primary cause of ill-health and mortality among children in developing countries. Mid-childhood is a dynamic period of physical growth and mental development of a child. Malnutrition in young children puts them at a higher risk of experiencing health problems such as stunted growth, increased susceptibility to infectious diseases and other morbidities. Methodology: Cross sectional study was conducted from June to September 2018 among 636 children who reported to Out Patient Department (OPD) counter of Mandya Institute of Medical Sciences (MIMS), Mandya in the age group of 5 – 10 years during the study period. Interview was done using a pre-tested, semi-structured questionnaire. Results: 433 (68.1%) children were normal and 203 (31.9%) were malnourished. Overweight and obesity was more common in higher socio-economic status (SES) and thinness & severe thinness was more in lower SES. Overweight and obesity was more among girls. Thinness and severe thinness was more among boys. Mothers knowledge regarding nutrition of their children and nutritive food for children was poor. Conclusion: 32% children were malnourished. Overweight and obesity was more among girls. Mothers had poor knowledge regarding nutritive food for children.